2021
DOI: 10.33961/jecst.2021.00059
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Full-Scale Pilot Model of a Cost-Effective Sodium Nickel-Iron Chloride Battery Over 40 Ah

Abstract: To fabricate a full-scale pilot model of the cost-effective Na-(Ni,Fe)Cl 2 cell, a Na-beta-alumina solid electrolyte (BASE) was developed by applying a one-step synthesis cum sintering process as an alternative to the conventional solid-state reaction process. Also, Fe metal powder, which is cheaper than Ni, was mixed with Ni metal powder, and was used for cathode material to reduce the cost of raw material. As a result, we then developed a prototype Na-(Ni,Fe)Cl 2 cell. Consequently, the Ni content in the Na-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Currently, the β -alumina ceramic is the standard electrolyte commercially used in high-temperature sodium batteries [110], although advanced formulations were investigated with promising results when applied in prototypal sodium-metal chloride cells [88,92,125]. Despite this, one of the main limitations of β -alumina is the poor ionic conductivity at low temperatures, which contributes to the total resistance of the cell and limits the operation of the batteries, particularly below 200 • C [35].…”
Section: Beta-alumina Solid Electrolytementioning
confidence: 99%
“…Currently, the β -alumina ceramic is the standard electrolyte commercially used in high-temperature sodium batteries [110], although advanced formulations were investigated with promising results when applied in prototypal sodium-metal chloride cells [88,92,125]. Despite this, one of the main limitations of β -alumina is the poor ionic conductivity at low temperatures, which contributes to the total resistance of the cell and limits the operation of the batteries, particularly below 200 • C [35].…”
Section: Beta-alumina Solid Electrolytementioning
confidence: 99%
“…While significant attention to Naβ"-alumina dates back as early as in the 1960s when sodium-sulfur batteries were originally developed by Weber and Kummer at the Ford Motor Company [1], the relatively high working temperature in a molten sodium-sulfur battery has significantly limited their applications and development, and soon, they were almost completely replaced by more popular lithium ion batteries in mobile applications. However, with increasing demands on large-scale energy storage due to climate change and the bloom of a solid-state battery, applications of Na-β"alumina are seemingly rising again because of the abundance of sodium as compared to lithium sources and the high ionic conductivity of about 1 S cm −1 in single crystal Na-β"alumina and 0.2-0.4 S cm −1 in polycrystalline β"-alumina at 300 • C [4][5][6][7][8][9][10]. For example, recently, Fertig et al have provided a detailed review on the potential revival of Na-β"-alumina for sodium solid-state batteries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ligon et al have reported large planar Na-β"-alumina solid electrolytes (150 mm in diameter) for next generation Na-batteries [5]. Lee et al have demonstrated a full-scale pilot model of a cost-effective sodium-nickel-iron chloride battery over 40 Ah using a Na-β"-alumina electrolyte [9]. Zhu et al have reported that by ion exchange, a Na-β"-alumina-containing composite electrolyte may be ion exchanged with molten salts to lithium-ion or silver-ion conducting electrolytes [11], which may further expand the application of Na-β"-alumina in other types of batteries.…”
Section: Introductionmentioning
confidence: 99%